Acrochordonichthys gyrinus, a new species of akysid catfish (Teleostei: Siluriformes) from Thailand - Vidthayanon, Chavalit; Ng, Heok Hee (Zootaxa, 2003)
Acrochordonichthys gyrinus, a new species of akysid catfish belonging to the A. ischnosoma species group, is described from the Chao Phraya River drainage in Thailand. It can be distinguished from congeners by a concave posterior margin of the pectoral fin and the unique combination of the following characteristics: head depth 9.8–11.4% SL; dorsal to adipose distance 7.4–8.6% SL; body depth at anus 8.3–10.5% SL; maximum width of humeral process 16.3% its length; and anterior margin of anal fin and posterior margin of adipose fin straight. This species represents the northernmost distribution of the genus.